Differentiation of maize breeding samples by β-carotene content - T. M. Satarova; V. V. Semenova; J. Zhang; H. Jin; B. V. Dzubetskii; V. Y. Cherchel (Regulatory Mechanisms in Biosystems, 2019)
Plant carotenoids are important micronutrients in the diet of humans and animals, since they act as precursors for the synthesis of vitamin A in animal cells. The most effective precursor to the vitamin A biosynthesis is β-carotene. Increasing the β-carotene content in maize grain as an important feed and food crop is an urgent task for plant selection. The purpose of this work was to differentiate maize breeding samples from the Dnipro breeding program by the β-carotene content in mature grain. Maize grain of 18 inbreds harvested in 2015 and 5 inbreds harvested in 2016 was researched. Determination of β-carotene content in matured dry grain was carried out after petroleum ether extraction and ultra performance liquid chromatography (UPLC) in the mobile phase of methanol/acetonitrile. The β-carotene content in the grain of genotypes from the Dnipro breeding program was on average 1.020 mg/kg for inbreds grown in 2015, and 0.672 mg/kg for inbreds grown in 2016. These values correspond to the β-carotene content in the grain of the majority of genotypes from world breeding programs selected by methods of classical selection. The inbred DKV3262 with white grain had the smallest content of β-carotene (0.076 mg/kg), while the yellow-coloured line DKD9066 had the highest one (2.146 mg/kg). The variation in the grain β-carotene content in different years of maize cultivation was noted. Inbreds of flint and semident maize showed the general tendency to increase the β-carotene content in grain compared with dent ones. The distribution of the studied inbreds on germplasm types showed the significant variation of β-carotene content in grain and the incidence of relatively high values in all germplasms analyzed. Inbreds containing more than 1.5 mg of β-carotene per 1 kg of grain, DK239, DK206A, DK212, DKD9066 and DKE-1, are emphasized as promising for the selection to increase the content of valuable micronutrients.